2021
DOI: 10.3389/fonc.2021.664928
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation in Children With Cancer or Hematopoietic Cell Transplantation: Single-Center Experience in 20 Consecutive Patients

Abstract: Extracorporeal membrane oxygenation (ECMO) is a rescue therapy for severe respiratory and/or circulatory failure. Few data exist on the potential benefit of ECMO in immunocompromised pediatric patients with cancer and/or hematopoietic cell transplantation (HCT). Over a period of 12 years, eleven (1.9%) of 572 patients with new diagnosis of leukemia/lymphoma and nine (3.5%) of 257 patients post allogeneic HCT underwent ECMO at our center. Five (45%) and two (22%) patients, respectively, survived to hospital dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Recent reports have indicated an ECMO success rate in pediatric settings of 20%–40% [ 12 , 13 ]. In the present study, we observed ICU and hospital survival rates of 29% and 24%, respectively, similar to previously reported survival rates [ 14 - 17 ]. In a previous analysis conducted at a single institution in South Korea, the survival rate among 15 adult patients with hematological malignancies and receiving ECMO was 0% [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Recent reports have indicated an ECMO success rate in pediatric settings of 20%–40% [ 12 , 13 ]. In the present study, we observed ICU and hospital survival rates of 29% and 24%, respectively, similar to previously reported survival rates [ 14 - 17 ]. In a previous analysis conducted at a single institution in South Korea, the survival rate among 15 adult patients with hematological malignancies and receiving ECMO was 0% [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Sixty-four manuscripts met search criteria and 24 were included as primary reports of pediatric HCT patients who underwent ECLS. These 24 reports included 11 single case reports (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), four single institution case series (28)(29)(30)(31), two multi-institution case series (32,33), and seven registry reports from Extracorporeal Life Support Organization (ELSO), Pediatric Heath Information System (PHIS), and Virtual Pediatric Systems (VPS) (14,15,(34)(35)(36)(37)(38). As patients included in these case reports, series, and registries are variably deidentified, we cannot exclude the possibility of patient overlap in these multiple manuscript formats.…”
Section: Resultsmentioning
confidence: 99%
“…Jensen et al (30) reported a cohort of n = 4 pediatric HCT patients treated with ECLS between 2000 and 2017 with three of the four surviving to hospital discharge. In 2021, Potratz et al (31) and Bridges et al (32) each reported an additional n = 9 children, of whom n = 3 and n = 2 survived, respectively. Di Nardo et al (28) reviewed a single center experience with 10 children, two surviving to hospital discharge.…”
Section: Case Seriesmentioning
confidence: 99%